New product development : Go rider (smart apps) / Cik Mohamad Zafri Che Sabudin ...[et al.] - Che Sabudin, Cik Mohamad Zafri; Zulkafli, Muhammad Nazmi; Abdullah, Azrul H'akimi; Hashim, Mohamad Hasif; Hashim, Addam (2019)
The name of the innovation: Go Rider Apps • The innovation is an applications (apps) that providing transport services via motorcycle • Serves as an easy online booking of motorcycle transport services. The purpose of the innovation is to :- • Provide convenience transport services • Provide fast transport services • Alleviate traffic jams by travelling via motorcycle • Effective methods of transport passenger and goods The target market :- • Urban community in Klang Valley How the idea was derived :- • Problems of traffic jams due to increasing amount of cars on the road • Reduce time on the road • Arrive at destination on time